Hollow Fiber Oxygenator Composition Has a Significant Impact on Failure Rates in Neonates on Extracorporeal Membrane Oxygenation: A Retrospective Analysis - Daniel, John M., IV; Bernard, Philip A.; Skinner, Sean C.; Bhandary, Prasad; Ruzic, Ana; Bacon, Matthew K.; Ballard, Hubert O. (Journal of Pediatric Intensive Care, 2018)
In extracorporeal life support (ECLS), there are two main types of oxygenators in clinical use for neonates: polymethylpentene (PMP) hollow fiber and polypropylene (PP) hollow fiber. A retrospective study was performed on neonates (n = 44) who had undergone ECLS for noncardiac indications from 2009 to 2015. Between the two groups (PMP n = 21, PP n = 23), the PP oxygenators failed 91% of the time, whereas the PMP oxygenators failed 43% of the time (p < 0.05). Analysis suggests PMP oxygenators are less prone to failure than PP oxygenators, and they require fewer number of oxygenator changes during a neonatal ECLS.
Keywords: extracorporeal membrane oxygenation; neonatal; oxygenator; complications